Pola Komunikasi Antarpribadi Antara Pelatih dan Siswa Sekolah Sepak Bola (SSB) Tuna Betawi Srengseng, Jakarta Barat - Munir, Muhammad Zidane; Simatupang, Sunengsih D. (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research examines the interpersonal communication patterns between coaches and students in the context of youth soccer development at the Tunas Betawi Soccer School (SSB) in Srengseng, West Jakarta. The study aims to understand how communication between coaches and students influences soccer coaching within the SSB environment. Qualitative research methods were employed, utilizing participant observation and interviews to collect data from several coaches and actively involved students in the soccer coaching program at SSB Tunas Betawi.Findings indicate that effective and supportive communication between coaches and students plays a crucial role in creating a positive learning environment and building strong relationships. This communication not only enhances the technical and tactical aspects of soccer coaching but also supports broader personal and social development among students. Coaches who can deliver instructions clearly, provide constructive feedback, and motivate students positively tend to create an atmosphere conducive to optimal learning. Furthermore, the interaction between coaches and students also significantly influences the development of students' character and mental attitudes towards sports.The implications of this study underscore the need for improving communication patterns in youth sports coaching contexts. This includes a better understanding of individual learning styles, emotional management, and motivating students to achieve their optimal potential in sports. These findings contribute significantly to the development of more effective coaching practices beneficial for children's development at SSB and other sports environments.